Sustainable service quality assessment of Chinese healthcare e-government: a multi-criteria decision framework based on SERVQUAL model and entropy-weight TOPSIS method - Xia, Yilin; Li, Bei; Yang, Jian; Guo, Weixi; Sun, Jianwei; Zeng, Xu; Zheng, Jing (Frontiers in Digital Health, 2025)
IntroductionHealthcare e-government plays a vital role in advancing the United Nations 2030 Agenda for Sustainable Development, by disseminating vital information and delivering essential services, particularly during the coronavirus disease 2019 (COVID-19) pandemic. China faces challenges within the context of health care, such as limited infrastructure and equitable healthcare access, underscoring the necessity of evaluating and improving the quality of healthcare e-government services.MethodsThis study proposes a novel multicriteria decision-making framework for systematically evaluating the quality of healthcare e-government services. The framework structurally extends the SERVQUAL model into 5 first-level and 31 s-level dimensions tailored to digital governance and integrates it with the entropy weight method and the technique for order of preference by similarity to ideal solution. This hybrid methodology enables objective, scalable, and theory-based assessment. To validate its effectiveness, the model was empirically applied to 17 Chinese municipal health commission websites in the period of 2019–2024 to validate its effectiveness.ResultsThe results revealed that empathy represents the most critical quality gap among the evaluated healthcare e-government services, while cross-platform interoperability has become a strategic focus for system improvement. These results highlighted that sustainable service quality is contingent on both robust technical infrastructure and human-centric factors.DiscussionThe proposed framework can offer policymakers a replicable decision-support tool by bridging the gap between operational performance and sustainable service delivery, particularly in developing regions. This provides practical insights into achieving digital healthcare transformation, contributing to the United Nations Sustainable Development Goals, offers a scalable evaluation approach for comparative research in digital governance, and promotes global e-government systems.